2019
DOI: 10.1080/12298093.2019.1687252
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Protoplast Preparation and Regeneration of a Medicinal Fungus Antrodia cinnamomea

Abstract: Antrodia cinnamomea is a unique medicinal fungus in Taiwan. It has been found rich in some pharmacologically active compounds for anti-cancer, hangover, and immune regulation etc. With the in-depth study of these components, it would be interesting and important to establish a molecular system for basic studies of A. cinnamomea. Thus, we would like to set up a foundation for this purpose by studying the A. cinnamomea protoplast preparation and regeneration. Firstly, we studied the optimization method of protop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…In the three fungal species tested, cell wall removal was successfully accomplished after fixation with either 4% formaldehyde or 4% formaldehyde + 0.25% glutaraldehyde. As reported previously (Li et al, 2017;Wu and Chou, 2019), the germination time of F. oxysporum conidia had a significant impact on the outcome of cell wall digestion, with longer germination times resulting in incomplete cell wall digestion that impaired the expansion process ( Supplementary Figure S2).…”
Section: Degradation Of the Cell Wall With Lytic Enzymes Enables Expasupporting
confidence: 72%
“…In the three fungal species tested, cell wall removal was successfully accomplished after fixation with either 4% formaldehyde or 4% formaldehyde + 0.25% glutaraldehyde. As reported previously (Li et al, 2017;Wu and Chou, 2019), the germination time of F. oxysporum conidia had a significant impact on the outcome of cell wall digestion, with longer germination times resulting in incomplete cell wall digestion that impaired the expansion process ( Supplementary Figure S2).…”
Section: Degradation Of the Cell Wall With Lytic Enzymes Enables Expasupporting
confidence: 72%
“…According to the previous references ( Flor-Parra et al, 2014 ; Wu et al, 2018 ; Wu and Chou, 2019 ; Jin et al, 2020 ), the fungal age and mycelium status were very important in the preparation of fungal protoplasts, which is the basis to prepare the protoplasts successfully. If the culture time of mycelium was too short, mycelium does not proliferate, leading to too little mycelium and insufficient protoplasts.…”
Section: Resultsmentioning
confidence: 99%
“…In the process of preparing fungal protoplasts, the main influencing factors are enzyme types and concentration, osmotic stabilizers, temperature, enzymatic digestion time, and fungal age ( Flor-Parra et al, 2014 ; Wu et al, 2018 ; Jin et al, 2020 ). Different species of fungi have different conditions for protoplasts preparation ( Wu and Chou, 2019 ). At present, there are a few reports on the preparation and regeneration studies of Eutypella species protoplasts to reference, which need to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of economy, time, and efficiency, results showed that 3 mg mL −1 Lysing enzyme and 2 mg mL −1 Yatalase were the optimal concentrations to use for protoplast release from strain LC5815. Protoplast quality is influenced by multiple factors including enzymolysis temperature and duration [ 24 , 25 ]. No obvious differences were seen in the number of released fungal protoplasts when the digestion reactions were incubated at temperature 25 °C or 28 °C.…”
Section: Resultsmentioning
confidence: 99%
“…If the osmotic pressure stabilizer concentration is too high, or too low, protoplast preparation and regeneration can be severely affected. The osmotic pressure stabilizer also affects enzyme activity, which indirectly affects protoplast yield [ 24 , 34 ]. In this study, we optimized the spore germination medium and time for strain LC5815.…”
Section: Discussionmentioning
confidence: 99%